THE COMPETENCIES MODEL OF ALPHA GENERATION: A MIX METHOD APPROACH IN EDUCATION AND TECHNOLOGY - Avianti , Widiya; Pitaloka, Endang; Affandi, Azhar (Jurnal Riset Bisnis dan Manajemen, 2026)
Human resource development for Generation Alpha is based on the concepts of education and technology, due to daily habits that are closely linked to technology. However, the work abilities of Generation Alpha, characterized by their adaptability to technology and strong desire to learn, are not yet fully balanced due to a lack of soft skills such as communication, leadership, and social empathy. Respondents in this study were taken from secondary school students born after 2010. Using a verifiable quantitative research method based on literature studies, it was revealed that the variable of psychological well-being functions as a mediator between digital literacy and work readiness as well as soft skills and work readiness.  It is understood that optimal digital and social skills for use in the workplace also depend on mental balance and the ability to manage stress.